SANGSI PELAKU PERNIKAHAN ILEGAL - Moh. Asy'ari Muthhar; Imam Musyafirudin (LPPM UNHASY, 2022)
This article is the result of library research. This research is included in the category of normative legal research. This research discussion aims to explain the istiḥān argument against the draft criminal sanctions law for perpetrators of illegal marriages. The researcher analyzed the data using istihsān bi al-maqāsid sharī'ah theory. The findings of this study are that the draft law regarding the provision of criminal sanctions against perpetrators of illegal marriages is not effectively implemented. This argument is based on the reading of legal material data with the theory of Istiḥsān bi maṣlaḥat al-mursalah. The legal reasoning put forward by Toeri istihsan is first, there are still many inadequate facilities in serving the implementation of Law Number 1 of 1974; second, less than optimal bureaucracy and background problems or motivation in carrying out marriages outside the institution of marriage registrar officials as well as conflicting government regulations with one another. The research data is read with the istiḥsān theory and results in the absence of mashlahah if the rules of criminal sanctions are applied. Keywords: Perpetrators of illegal marriages, Draft law, istiḥsān Daftar Pustaka Al Amin, Habibi.